Production Form and Process Jambe Kusuma Kendal Batik in The Context of Women Empowerment of Ex-Tkw in Kendal District (Catharsis, 2022)
Batik is actually an activity that cannot be separated from people's lives in every region in Indonesia, as well as the lives of the people of Kendal Regency who always coexist with batik activities. It is estimated that batik came to Kendal Regency by a batik entrepreneur from Pekalongan in the 19th century. The reappearance of batik in Kendal Regency was marked by the emergence of a group of batik entrepreneurs, one of which was called the Jambe Kusuma Batik Studio. The members of this studio are women, especially batik artisans whose backgrounds have worked abroad as female workers (TKW). Low wages and limited job opportunities force women to work away from their families. This condition makes a number of parties concerned so that many regional and private service agencies are looking for solutions in order to empower ex-TKW so that they can maximize their potential with various activities, one of which is through batik activities. The problem studied is the influence of the socio-economic environment of the Jambearum Village community on the aesthetic expression of batik works. The research location was located at the Jambe Kusuma Batik Studio in Jambearum Village, Patebon District, Kendal Regency with the research target being ex-Women Workers (TKW) in Kendal Regency in the batik production process. The Jambe Kusuma batik motif is dominated by endemic flora motifs found in Kendal Regency and marine fauna. The integrity of the turtle and godhong mbako motifs can be found in the turtle decoration which is harmonized with godhong mbako. The color integrity in image one lies in the background color which is dominated by blue to gray. The protrusion of the motif is found in the shape of the turtle which uses a decorative approach but can be identified by the structure of the subject so that it looks realistic. Jambe Kusuma Batik is the result of creativity that continues to experience development. Women's empowerment can be pursued through improving the quality of education, skills and economic conditions. The goal of overall empowerment can ideally increase gender development which creates a balance.